Nutritional Status Of Toddler In Agricultural Areas - Yusnitasari, Engelina; Tia Rachman Cahyaningrum; Nabila Meyra Anindita; Kurniyawan, Enggal Hadi; Dicky Endrian Kurniawan; Alfid Tri Afandi; Kholid Rosyidi Muhammad Nur (Rajaki of Tulip Medika Publisher, 2024)
Introduction: Nutritional status in toddlers has an important role in the growth and development of toddlers, which is related to health and intelligence. Nutritional status in toddlers involves measuring height, weight, and age. Providing insufficient or excessive nutrition can cause poor nutritional status. Objective: Find out the nutritional status of toddlers and the problems of malnutrition that occur in toddlers in agricultural areas. Method: This research uses the literature review method or literature review. Literature sources were collected from research journal databases and the internet, focusing on Google Scholar, Science Direct, and Pubmed for publications between 2019 and 2024. Results: The nutritional status of toddlers is influenced by various factors, including parenting patterns, family roles, nutritional consumption, and the environment. Balanced nutrition education can increase understanding among mothers of toddlers. Toddlers in farming families and non-fishing communities have a higher prevalence of stunting. Conclusion: The nutritional status of children under five in agricultural areas still needs to improve. Comprehensive interventions need to always be carried out by ensuring that toddlers receive nutritional intake and a healthy environment for optimal growth and development.